Mineralogy and petrology of Belgica-7904: A new kind of carbonaceous chondrite from Antarctica - Tomeoka, Kazushige (National Institute of Polar Research, 1990)
P(論文) A mineralogical and petrological study of Belgica-7904 (B-7904) shows that it can be classified into the CM group. B-7904 has a variety of chondrules and aggregates, where pyroxenes and mesostasis glass are completely replaced by phyllosilicates, but olivine remains little altered. It has a high abundance of troilite; most occur in submicron to micron grains dispersed in the matrix. Minor taenite occurs, but magnetite is rare and tochilinite is absent. The phyllosilicates have relatively high Na contents and lower (Mg+Fe)/(Si+Al) ratios than serpentine; thus, they may be intergrowths of serpentine and a smectite-like phyllosilicate. Microprobe analyses of the phyllosilicates show high analytical totals relative to ordinary phyllosilicates, being consistent with the idea that they were dehydrated by heating. The fine troilite grains in the matrix may have been transformed from a thermally labile phase such as tochilinite during thermal metamorphism. The opaque mineral assemblage suggests that the thermal metamorphism occurred in a reduced condition. B-7904 and Y-86720 are mineralogically similar, although the former is less affected by aqueous alteration than the latter. They were probably derived from similar precursors and experienced aqueous alteration and thermal metamorphism in a common environment. These meteorites and ordinary CM chondrites apparently experienced distinct alteration histories, suggesting that they came from different regions in a parent body or different parent bodies. departmental bulletin paper